Mechanochemical Aza-Vinylogous Povarov Reactions for the Synthesis of Highly Functionalized 1,2,3,4-Tetrahydroquinolines and 1,2,3,4-Tetrahydro-1,5-Naphthyridines - José Clerigué; M. Teresa Ramos; J. Carlos Menéndez (Molecules, 2021)
The aza-vinylogous Povarov reaction between aromatic amines, α-ketoaldehydes or α-formylesters and α,β-unsaturated dimethylhydrazones was carried out in a sequential three-component fashion under mechanochemical conditions. Following extensive optimization work, the reaction was performed on a vibratory ball mill operating at 20 Hz and using zirconium oxide balls and milling jar, and afforded 1,2,3,4-tetrahydroquinolines and 1,2,3,4-tetrahydro- 1,5-naphthyridines functionalized at C-2, C-4 and also at C-6, in the latter case. This protocol generally afforded the target compounds in good to excellent yields and diastereoselectivities. A comparison of representative examples with the results obtained under conventional conditions revealed that the mechanochemical protocol affords faster Povarov reactions in comparable yields using a solvent-less environment.